PLASMONIC MODE CONFINEMENT IN InAs–SiO_2–Si WAVEGUIDE IN TERAHERTZ REGION - Hakobyan, H.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
The dispersion relation of a novel semiconductor-gap-dielectric waveguide in terahertz range are investigated. It is shown that InAs–SiO2–Si structure supports strongly confined guided mode with а sizes 0.0016 λ × 0.02 λ at 1 THz.